FINANCIAL ASPECTS OF CURRENT ASSETS MANAGEMENT IN SERBIAN ECONOMY - Aničić, Jugoslav; Simić, Nataša; Petrović, Vesna; Aničić, Dušan (Journal of process management and new technologies, 2017)
Efficient current assets management should provide optimum level of company’s net current assets as interrelation between current assets and short-term liabilities. The companies whose short-term liabilities are not proportionate to cashable current assets face the problem of insolvency and all negative consequences caused by insolvency. Rate of return to total assets measures how good is the management’s use of the company property for the purpose of creating operating profit, regardless of the fact how these assets are financed. Serbian economy is burdened by insolvency and significant indebtedness under unfavorable loan terms, so adequate attention has to be dedicated to the matters of the structure of operating property and its financing in order to improve competitiveness and efficiency of business.